Analysis of Interactions among Greenhouse Gas Emissions, Carbon Sinks, and Food Security in China’s Agricultural Systems - Wenjie Yang; Xiaoyun Mo (Agriculture, 2024)
Reducing greenhouse gas (GHG) emissions and increasing the size of carbon sinks are closely related to food security in agricultural systems. This study conducted an in-depth data analysis of previous studies to explore the dynamic causal relationships among the reduction of emissions, carbon sink increases, and food security in agricultural systems. The fixed-effect regression model, causality tests, PVAR model, impulse response functions, and variance decomposition were used to explore correlations among the three variables. The results show that the national average carbon sinks surged from 2662.194 Mg in 2000 to 4010.613 Mg in 2020, with the food security index concurrently climbing from 0.198 to 0.308. Moreover, GHG emissions exhibited a negative growth rate from 2016 onwards, yet the 2020 mean remained 142.625 Mg above the 2000 baseline. The agricultural “three subsidies” reform has not directly promoted food security, but significantly inhibited GHG emissions. However, conflicts exist between emissions reduction and carbon sinks increase in agricultural systems and food security. At the whole level, changes in carbon sinks only have a positive effect on the increase in GHG emissions, whereas changes in GHG emissions have a positive effect on both carbon sinks and food security. Changes in food security strongly inhibit the increase in carbon sinks. This relationship varies among distinct grain functional zones. Policy objectives should be coordinated, target thresholds set, and policies classified according to different functional orientations, to achieve a win–win situation for food supply and low-carbon development.